Inovasi sebagai Mekanisme Strategis Penghubung Financial Technology dan Financial Literacy terhadap Kinerja UMKM - Dinda Ilyatur Rosyidha; Mardiana Mardiana (Politeknik Ganesha Medan, 2026)
This study examines the inconsistency of empirical findings regarding the effects of Financial Technology (Fintech) and Financial Literacy on the performance of Micro, Small, and Medium Enterprises (MSMEs) in developing economies. While Financial Literacy is widely recognized as a fundamental capability that consistently enhances firm performance, empirical evidence on Fintech remains mixed and often insignificant. This inconsistency suggests that Fintech adoption does not automatically translate into improved MSME performance. Departing from prior studies that predominantly assume a direct and linear relationship, this study positions innovation as a strategic transmission mechanism that explains how Fintech and Financial Literacy are transformed into performance outcomes. This research employs a quantitative approach using primary data collected from 225 MSME owners in Malang City through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal a paradoxical result: Fintech does not have a significant direct effect on MSME performance, yet it exerts a significant indirect effect through innovation, indicating full mediation. In contrast, Financial Literacy has a significant positive effect on MSME performance both directly and indirectly through innovation, suggesting partial mediation. The theoretical contribution of this study lies in reconceptualizing innovation not merely as an outcome of digital adoption, but as a strategic mechanism that determines the effectiveness of financial and digital capabilities in generating performance gains. From a practical perspective, the findings imply that MSME development strategies should integrate financial literacy enhancement, effective Fintech utilization, and innovation capability strengthening to achieve sustainable performance improvements.